The neuronal ceroid lipofuscinoses - Hofmann, Sandra (Henry Stewart Talks, 2007)
Clinical features of the neuronal ceroid lipofuscinoses, Genetics, Genotype/phenotype correlations, Protein epidemiology, Mechanisms of neurodegeneration, Treatment approaches
Updated at 2016/07/27